Guiding stem cells for cutaneous repair - Shivani Desai; Juilee Jagtap; Shivani Sainani; Ramesh Bhonde (Elsevier, 2023)
The significance of mesenchymal stem cells (MSCs) for tissue repair and regeneration is widely recognized. The pleiotropic nature of MSCs is demonstrated by their potential for proliferation and differentiation, and paracrine secretions, thereby making them ideal candidates for cell replacement therapy. Tissue resident MSCs are engaged in homeostasis under normal wear and tear. However, stem cell therapy may be applicable if damage cannot be repaired by normal homeostatic mechanisms. The safety of MSCs has been clearly established in clinical trials but their efficacy remains questionable. The efficacy of MSCs depends on several factors, such as their viability, functional status in terms of secretome secretions, and the in-vivo scenario after transplantation. The performance of MSCs is regulated by their micro-environmental conditions and cues. The so-called MSC niche comprises physical, chemical, and biological components, which play key roles in determining the fate of MSCs. MSCs scaled up for transplantation purposes comprise a disorganized mass of cells, which needs to be directed to perform the required function. Thus, MSCs need to be directed toward an expected target activity in human patients. This review focuses on the various methods that can be used to guide stem cells for cutaneous repair.